A formação dos precedentes no sistema de recursos repetitivos - Lísias, Andressa Paula Senna (2021)
Much has been studied in Brazil on precedents, especially after the CPC / 15 came into force. Such studies, in the doctrinal sphere or the scientific survey universe, are dedicated to examining the binding effects, based on article 927 of the Code. Considering this and recognizing the relevance of theoretical discussions in relation to the binding, we chose other focus for this research: the decision-making process. As it would not be possible to approach all the itens of article 927, because each mechanic there is particular, we chose only the technique of repetitive appeals as our object. As these judgments will be standard for other repeated cases, investigating and highlighting their production conditions is so important as their subsequent repercussions. In this survey, we seek, then, to identify these conditions based on the Federal Constitution (CF/88) and the Brazilian Civil Procedure Code of 2015 (CPC/15), and understand if they were properly implemented and regulated. Thus, we think optimal levels of advertising, contradiction, equality and participation would make the decision-making process legitimate, democratic and constitutional, at all stages. On the other hand, the search for this ideal proportion of fundamental values and rights shows, as the analysis progresses, some points of deficiency in the current model. As will be seen, the research morphology frequently explores the tension between both sides of the problem: formation and deformation. And it makes sense, because, after all, the Brazilian system of precedents is being built, it is not quite complete nowadays. It is very possible that its consolidation, next years, will still accommodate certain adjustments - some of them legislative - that will improve it. Critical reflection helps to awaken this construction. Having done the path proposed in this survey, we conclude precedent-making process can contribute to achieving the stability and consensus of the judicial solution